Myocardial injury is decreased by late remote ischaemic preconditioning and aggravated by tramadol in patients undergoing cardiac surgery: a randomised controlled trial - Wagner, Robert; Piler, Pavel; Bedanova, Helena; Adamek, Petr; Grodecka, Lucie; Freiberger, Tomas (Interactive cardiovascular and thoracic surgery, 2010)
The purpose of this study was to test, whether the late phase of remote ischaemic preconditioning (L-RIPC) improves myocardial protection in coronary artery bypass grafting (CABG) with cold-crystalloid cardioplegia and whether preoperative tramadol modifies myocardial ischaemia-reperfusion injury using the same group of patients in a single-blinded randomized controlled study. One hundred and one adult patients were randomly assigned to either the L-RIPC, control or tramadol group. L-RIPC consisted of three five-minute cycles of upper limb ischaemia and three five-minute pauses using blood pressure cuff inflation 18 hours prior to the operation. Patients in the tramadol group received 200 mg tramadol retard at 19:00 hours, the day before the operation and at 06:00 hours. Serum troponin I levels were measured at eight, 16 and 24 hours after surgery. Myocardial samples for inducible and endothelial nitric oxide synthases (iNOS, eNOS) estimation were drawn twice: before and after cannulation for cardiopulmonary bypass from the auricle of the right atrium. We found that L-RIPC can reduce injury beyond the myocardial protection provided by cold-crystalloid cardioplegia, and tramadol worsened myocardial injury after CABG. Expressions of iNOS were increased in the control (significantly) and L-RIPC groups and dampened in the tramadol group.
Keywords: výsledek terapie; koronární bypass; Male; biologické markery; Hypothermia, Induced; Nitric Oxide Synthase Type III; Biomarkers; přivykání k ischémii; Potassium Compounds; sloučeniny draslíku; Česká republika; Heart Diseases; Coronary Artery Bypass; Analgesics, Opioid; Myocardium; Nitric Oxide Synthase Type II; Aged; Ischemic Preconditioning; mužské pohlaví; senioři; tramadol; opioidní analgetika; Czech Republic; Time Factors; terapeutická hypotermie; Treatment Outcome; senioři nad 80 let; troponin I; Single-Blind Method; Tramadol; lidé; Heart Arrest, Induced; ženské pohlaví; synthasa oxidu dusnatého, typ III; Humans; jednoduchá slepá metoda; časové faktory; nemoci srdce; Aged, 80 and over; Troponin I; synthasa oxidu dusnatého, typ II; vyvolaná zástava srdce; Female; lidé středního věku; myokard; Middle Aged